Analyzing The Role of English Pop Culture in Shaping Students' Language Learning Motivation - Ketut Purwantoro; Tri Mulyani Wahyuningsih; Budi Santosa (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2025)
This study aims to analyze the role of English-language pop culture in shaping the motivation to learn English in students. Pop culture, which includes music, movies, television series, and social media, is part of popular culture that is growing rapidly and influencing the lifestyles and habits of the younger generation (Storey, 2018). Using qualitative methods through in-depth observation and interviews with high school students, the study found that exposure to British pop culture increased students' interest in learning the language. However, problems were also found in the learning environment such as the lack of integration of popular media in teaching materials and limited support from teaching staff. The main objective of this study is to understand how elements of pop culture can be used positively in supporting the language learning process. The results of the study show that a contextual approach based on students' interests can be an effective strategy to increase motivation to learn languages.